(untitled) (Jurnal Ilmu Manajemen dan Bisnis, 2025)
Adaptive strategic leadership is crucial in driving innovation, especially for Micro, Small and Medium Enterprises (MSMEs) in the creative sector that operate in a dynamic and uncertain business environment. This study aims to analyze the role of adaptive strategic leadership in developing the innovation capacity of creative sector MSMEs in Indonesia. Using a qualitative approach with a systematic literature study, data was collected from various relevant accredited national journals. The results show that adaptive strategic leadership, characterized by the ability to adapt to change, foster organizational learning, and facilitate rapid decision-making, signiﬁcantly contributes to improving the innovation capacity of MSMEs. Adaptive leaders are able to identify new opportunities, manage risks, and create an environment conducive to experimentation and creativity. The implications of this study highlight the importance of developing adaptive leadership competencies for creative sector MSME actors to ensure sustainability and competitiveness in the global market. This research provides theoretical contributions by enriching the literature on leadership and innovation in the context of MSMEs, as well as practical implications for leadership training and development programs in the creative MSME sector.